Market access asymmetry in food trade - Alessandro Olper; Valentina Raimondi (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
Using a bilateral trade equation derived from a monopolistic competition model, we investigated market access reciprocity in food trade among the US, Canada, the EU and Japan. We explore country and industry-specific market access asymmetry through the border effect approach, re-challenging the underlying main explanations. Our findings reveal marked asymmetry in reciprocal trade openness; indeed, access to the food markets of the US and Japan appears significantly easier than reciprocal access to both Canada and, especially, the EU. Policy trade barriers, firstly in the firms of NTBs, the degree of product differentiation and `home bias?in preferences, are all important factors in explaining border effects. Moreover, several stylized facts suggest that border effect interpretation should also be based on political economy arguments.
Keywords: F13; F14; Q17; 330; gravity; market access; asymmetry; food trade; NTBs; Lebensmittelhandel; Markteintritt; Grenze; Nichttarifäre Handelshemmnisse; Gravitationsmodell; USA; Japan; Kanada; EU-Staaten